THE EFFECT OF HUMAN RELATION, LOCUS OF CONTROL AND ORGANIZATIONAL CULTURE ON OCB WITH CONSUMER SATISFACTION AS INTERVENING VARIABLES (STUDY CASE AAT PT SUKA FAJAR, VETERAN PADANG) - Suriyana, Nofsri; Nandan Limakrisna; Andri Wijaya, Ronni (Dinasti Publisher, 2020)
The purpose of this study is to determine the influence of Human Relations, Locus Of Control, and Organizational Culture on OCB with Customer Satisfaction. The method of collecting data analysis uses a questionnaire, with a sample of 50 respondents. The data analysis method used is multiple linear regression. The result shows that Human Relations has positive and significant effect on customer satisfaction, with significant level of (0.014 <0.05). Locus of Control has significant effect on customer satisfaction, with significant level (0.038 <0.05). Organizational culture has significant effect on customer satisfaction, with significant level (0.016> 0.05). Human Relationship has significant effect on Ocb, with significant level (0.047 <0.05). Finally, the writer suggests that the company PT Suka Fajar Company increase the way of service for customer satisfaction or improve the way products sold to consumers, or increase competition in sales so that consumers feel satisfied with the company. Furthermore, enhance the way of marketing in a way that attracts customers to the company.